Magnetic Nanoparticles Immobilization and Functionalization for Biosensor Applications - M. B. Mejri; A. Tlili; A. Abdelghani (International Journal of Electrochemistry)
We describe an approach for E. coli bacteria detection using an electrochemical immunosensor. The immunosensor was based on functionalized magnetic nanoparticles immobilized onto bare gold electrode. Cyclic voltammetry and impedance spectroscopy was performed before and after magnetic nanoparticles deposition. The magnetic nanoparticles functionalized with anti-E. coli polyclonal antibody were used for bacteria detection. Lytic T4-phage was used to confirm the success recognition of bacteria with the developed immunosensor. The specificity of the immunosensor was tested against Enterococcus faecium bacteria. A limit detection of 103 CFU/mL E. coli bacteria was obtained with a good reproducibility.